Eliminating hunger and reducing poverty- Three perspectives: IFPRI 2006-2007 Annual Report Essay - von Braun, Joachim; Patel, Amrita; Soyinka, Wole (International Food Policy Research Institute, 2007)
Reducing poverty and ending hunger seem to be becoming more difficult goals to achieve. Although the world is a lot richer today than it was a decade ago, the numbers of poor and hungry people are declining more slowly. Are new approaches needed to reduce poverty and hunger? The first Millennium Development Goal focuses attention on cutting the proportions of poor and hungry people in half by 2015, but what will become of the people not addressed by that goal—the other half left behind? The three essays that follow explore the challenges the world faces in reducing poverty and hunger in a sustainable way. In their different emphases—local, national, and global; economic and cultural; growth and social protection; traditional and new actors—the essays provide new views on what needs to be done now to reduce hunger and poverty faster.